Relocation and dislocation: civilian, refugee, and military movement as factors in the disintegration of postwar China, 1945-49 - Mitter, R (Cambridge University Press, 2022)
This article argues that massive human displacement was one of the defining factors in China’s immediate postwar period (1945-49). It shows that at least three distinctive groups were dispersed during the wartime years and needed to be resettled after the war ended in August 1945: civilian refugees, administrators who had been relocated to the temporary capital at Chongqing, and troops transferred in anticipation of an upcoming civil war between the Nationalists and the Communists. The article argues that China’s new sovereign status in 1945 was paradoxically a source of weakness when it came to resettlement and reconstruction, as China sought international funds to undertake its own reconstruction, but could not demit responsibility to an external actor to organize matters as the US did in western Europe. A growing sense of anomie and unsettlement prevented resettlement and China remained a zone in which international and domestic conflict came together. Both sets of factors shaped the dislocation that destroyed the possibilities of a stable resettlement in China after the great displacement of wartime.